Wardium ponticum sp. n. (Cestoda, Cyclophyllidea, Hymenolepidoidea), a Parasite of Pratincole (Glareola pratincola) from the Black Sea Coas - Kornyushin, V.V.; Georgiev, B.B.; Greben, O.B. (Вестник зоологии, 2012)
The new species Wardium ponticum Kornyushin, Georgiev et Greben, sp. n. (Aploparksidae Mayhew, 1925) parasitic in pratincole (Glareola pratincola Linnaeus, 1766) from Bulgaria and Ukraine is described. The species is characterized by 10 aploparaksoid hooks, 9—10 mm long, and clearly differs from all congeneric species by the shape and armament of the cirrus.